Exploring the progenitors of brightest cluster galaxies at z ∼ 2 - Zhao, Dongyao; Conselice, Christopher J.; Aragón-Salamanca, Alfonso; Almaini, Omar; Hartley, William G.; Lani, Caterina; Mortlock, Alice; Old, Lyndsay (Oxford University Press, 2017)
We present a new method for tracing the evolution of brightest cluster galaxies (BCGs) from z ∼ 2 to z ∼ 0. We conclude on the basis of semi-analytical models that the best method to select BCG progenitors at z ∼ 2 is a hybrid environmental density and stellar mass ranking approach. Ultimately, we are able to retrieve 45 per cent of BCG progenitors. We apply this method on the Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey, Ultra Deep Survey data to construct a progenitor sample at high redshift. We furthermore populate the comparisons in local Universe by using Sloan Digital Sky Survey data with statistically likely contamination to ensure a fair comparison between high and low redshifts. Using these samples we demonstrate that the BCG sizes have grown by a factor of ∼3.2 since z ∼ 2, and BCG progenitors are mainly late-type galaxies, exhibiting less concentrated profiles than their early type local counterparts. We find that BCG progenitors have more disturbed morphologies. In contrast, local BCGs have much smoother profiles. Moreover, we find that the stellar masses of BCGs have grown by a factor of ∼2.5 since z ∼ 2, and the star formation rate of BCG progenitors has a median value of 13.5 Mʘ yr‾¹, much higher than their quiescent local descendants. We demonstrate that over z = 1–2 star formation and merging contribute equally to BCG mass growth. However, merging plays a dominant role in BCG assembly at z ≲ 1. We also find that BCG progenitors at high z are not significantly different from other galaxies of similar mass at the same epoch. This suggests that the processes which differentiate BCGs from normal massive elliptical galaxies must occur at z ≲ 2.